2009
DOI: 10.1080/19390210902861833
|View full text |Cite
|
Sign up to set email alerts
|

Practices, Attitudes, and Beliefs Regarding Dietary Supplements Among Florida's Dietitians and Nurses

Abstract: This study investigated the practices, attitudes, and beliefs of Florida's nurses and dietitians regarding dietary supplements (DS). Eighty-nine dietitians and 64 nurses responded to a self-reported online survey about nutrient-based supplements, defined as nutrients taken to supplement the diet for enhancing health, and herbal supplements, defined as plants used for enhancing health rather than food seasoning. Personal use of nutrient-based supplements for treatment of a health condition was higher among nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
(98 reference statements)
1
10
3
Order By: Relevance
“…Similarly, a study conducted by Lederman et al on healthcare professionals in the USA found that 66 % of the dietitians used dietary supplements to protect their health, 42 % to treat diseases and 19 % to enhance physical and mental performance (25) . The small-sample (n 95) study conducted on dietitians in the Netherlands found that 38 % of the participants frequently used dietary supplements to protect the health, 22 % to treat diseases and 13 % to enhance physical and mental performance.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Similarly, a study conducted by Lederman et al on healthcare professionals in the USA found that 66 % of the dietitians used dietary supplements to protect their health, 42 % to treat diseases and 19 % to enhance physical and mental performance (25) . The small-sample (n 95) study conducted on dietitians in the Netherlands found that 38 % of the participants frequently used dietary supplements to protect the health, 22 % to treat diseases and 13 % to enhance physical and mental performance.…”
Section: Discussionmentioning
confidence: 96%
“…The reasons for using dietary supplements were found to be maintaining bone health (58%), improving overall health, leading a healthy life (53%), and eliminating nutrient deficiencies (42%) due to malnutrition (23) . Similarly, a study conducted by Lederman et al on healthcare professionals in the United States found that 66% of the dietitians used dietary supplements to protect their health, 42% to treat diseases, and 19% to enhance physical and mental performance (25) . The small-sample (n=95) study conducted on dietitians in the Netherlands found that 38% of the participants frequently used dietary supplements to protect the health, 22% to treat diseases, and 13% to enhance physical and mental performance.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations